PENGARUH PENYIMPANAN KACANG TANAH DI RUMAHTANGGA TERHADAP KANDUNGAN AFLATOXIN - Muhilal Muhilal; Djiteng Roedjito (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1971)
Pengaruh penjimpanan katjang tanah dirumah tangga terhadap kandungan aflatoxin. (The aflatoxin contents of home-stored peanuts). To determine the limit of storage time of peanut at homes to prevent contamination by aflatoxin, samples of peanut were stored at homes in urban and rural communities. It was found that peanut started to contain aflatoxin in the tenth week, and by the 14th week the content had exceeded the safe level of 30 ppb. Drying peanut to eight per cent water content then storing them in tins with waxed covers may prevent aflatoxin contamination for 20 weeks. Aflatoxin ialah racun yang dihasilkan oleh cendawan Aspergillus flavus (1) yang banyak terdapat pada bahan makanan yang bercendawan. Bahaya toxin ini ialah dapat mengakibatkan kerusakan hati yang biasanya disusul oleh kematian dalam waktu singkat. Bila racun ini terkonsumsi dalam jumlah sedikit tetapi dalam waktu lama, akibat yang khas ialah kanker hati primer (2).